Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 3876 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Sylvilagus floridanus (J.A.Allen, 1890)", "HasCoordinate is true", "HasGeospatialIssue is false", "Year is greater than or equal to 1960" ] } The dataset includes 3876 records from 69 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0014908-160311141623029/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences